Contribution Of Arm Strength And Hand Coordination Towards The Ability Of The Patch Drive At The Badminton Club FIK UNP - Rosyadi, Ilham; Pratama, Yuda; Permana, Jatra (Jurnal Guru Peneliti Professional, 2017)
The problem of this research is the low drive ability of the badminton club players UKO FIK UNP. This study aims to see the contribution of Arm Muscle Strength Endurance and Hand-Eye Coordination with the Badminton Drive Ability of UKO FIK UNP. his research is correlational. The population in this study were players in the badminton club UKO FIK UNP, the entire population sampled amounted to 30 people. The results of data analysis showed that the contribution of arm muscle strength endurance with the ability to hit the drive was 13.18%, the contribution of eye-hand coordination with the ability to hit the drive was 23.04%.Contribution of Arm Muscle Strength Endurance and Hand-Eye Coordination to the Ability of Punch Drive = 24.50%.